Adaptation, Resilience, and Secure Attachment States of Mind in Young South African Female Students Exposed to Intimate Partner Violence in Childhood - Bain, Katherine (Journal of interpersonal violence, 2021)
Much research details the psychological risks to individuals exposed as children to intimate partner violence (IPV). However, resilience has been a neglected area of study within this population. This article details adaptive responses in six participants exposed to IPV in childhood. Adult attachment interviews (AAI) and follow-up semi-structured interviews analyzed using an interpretive thematic analysis revealed common themes relating to psychological defenses and adaptive strategies. Despite exposure to IPV in childhood, these six women were found to have secure attachment states of mind. Resilience was found not to be necessarily synonymous with the absence of distress. Despite the presence of suffering, it remained strongly associated with adaptive, robust defenses to manage distress and to retain caregiving relationships with parents. These defenses appeared to provide participants with ways to survive their traumatic environments and to remain connected to needed but frightening caregiving figures, and facilitated processing of trauma. Adaptation often entailed using compliance and caregiving responses in childhood in response to role reversal in parent–child relationships, but also the relinquishing of these roles in adulthood. Participants’ abilities to coherently acknowledge and discuss their early experiences and retain compassion for their parents seemed linked to their abilities to attain some distance from troubling aspects of their pasts. In doing so, they separated from the unstable relationships of their parents, which fostered transitions to more integrated states of mind.